A Principle Component Analysis of Galaxy Properties from a Large, Gas-Selected Sample - Yu-Yen Chang; Rikon Chao; Wei-Hao Wang; Pisin Chen (Advances in Astronomy)
Disney et al. (2008) have found a striking correlation among global parameters of Hi-selected galaxies and concluded that this is in conflict with the CDM model. Considering the importance of the issue, we reinvestigate the problem using the principal component analysis on a fivefold larger sample and additional near-infrared data. We use databases from the Arecibo Legacy Fast Arecibo L-band Feed Array Survey for the gas properties, the Sloan Digital Sky Survey for the optical properties, and the Two Micron All Sky Survey for the near-infrared properties. We confirm that the parameters are indeed correlated where a single physical parameter can explain 83% of the variations. When color (g-i) is included, the first component still dominates but it develops a second principal component. In addition, the near-infrared color (i-J) shows an obvious second principal component that might provide evidence of the complex old star formation. Based on our data, we suggest that it is premature to pronounce the failure of the CDM model and it motivates more theoretical work.